P854 Insights into alteration of gut microbiota in inflammatory bowel disease patients with and without Clostridium difficile infection. (25th January 2019) - Chen, D; Li, Y; Sun, H; Xiao, M; Lv, N; Liang, S; Tan, B; Zhu, B
Abstract: Background: Clostridium difficile infection (CDI) is common in inflammatory bowel disease (IBD) due to gut microbial dysbiosis. Our aim was to investigate the trend of gut microbial changes in IBD patients with CDI. Methods: The faecal microbiota of 21 active Crohn's disease (CD) patients without CDI (Group CD1， n = 13 ) with CDI (Group CD2, n = 8), 30 active ulcerative colitis (UC) patients without CDI (Group UC1, n = 19 ) and with CDI (Group UC2, n = 11) and 40 healthy controls (HC), was studied using 16S ribosomal RNA (rRNA) gene sequencing and metagenomics. Besides, Group IBD1 was defined as IBD without CDI ( n = 32), while IBD2 was defined as IBD with CDI ( n = 19). Results: (1) The α diversity was decreased in IBD patients compared with HC. But there was no significant difference between IBD patients with and without CDI. (2) The inter-group variability in community structure byβdiversity analysis using Principal Co-ordinates Analysis (PCOA) showed a clear separation between IBD patients with HC. But IBD patients with and without CDI could not be separated. (3) Relative abundance of bacteria at the genus level show different global composition in IBD patients with or without CDI and HC to some extent. (4) In UC patients, compared with UC without CDI, UC patients with CDI had lower abundance of bacilli and coriobacteriales OTUs at class level, lower abundance of coriobacteriales OTUs at order level and lower abundance of subdoligranulum and fusicatenibacter OTUs at genus level. (5) Metagenomics revealed that Bifidobacterium dentium, Pediococcus lolii, Clostridiales bacterium, Flavonifractor plautii, Pseudoramibacter alactolyticus, Anaerostipes caccae, Anaerostipes unclassified, Faecalibacterium prausnitzii and Edwardsiella tarda were positively associated with CDI. Conclusions: IBD especially UC patients with CDI is associated with a more pronounced microbial dysbiosis than patients without CDI, with specific alterations in intestinal microorganisms.